Cover crop residue components and their effect on summer annual weed suppression in corn and soybean. Issue 3 (18th May 2020) - Pittman, Kara B.; Barney, Jacob N.; Flessner, Michael L.
Abstract: Cover crop residue can act as a mulch that will suppress weeds, but as the residue degrades, weed suppression diminishes. Biomass of cover crop residue is positively correlated to weed suppression, but little research is available regarding the composition of cover crop residue and its effect on weed suppression. Field experiments were conducted to determine the impact of cover crop residue properties (i.e., total carbon, total nitrogen, lignin, cellulose, and hemicellulose) on summer annual weed suppression and cash crop yield. Cover crop monocultures and mixtures were planted in the fall and designed to provide a range of biomass and residue properties. Cover crops were followed by corn ( Zea mays L.) or soybean [ Glycine max (L.) Merr.]. At termination, cover crop biomass and residue components were determined. Biomass ranged from 3, 640 to 8, 750 kg ha −1, and the carbon-to-nitrogen (C:N) ratio ranged from 12:1 to 36:1. As both cover crop biomass and C:N ratio increased, weed suppression and duration of suppression increased. For example, a C:N ratio of 9:1 is needed to suppress redroot pigweed ( Amaranthus retroflexus L.) 50% at 4 wk after termination (WAT), and that increases to 16:1 and 20:1 to have 50% suppression at 6 and 8 WAT, respectively. Similarly, with biomass, 2, 800 kg ha −1 is needed for 50% A. retroflexus suppression at 4 WAT, which increases to 5, 280 kg ha −1 and 6, 610 kg ha −1 needed for 50% suppression at 6 and 8 WAT, respectively. In general, similar trends were observed for pitted morningglory ( Ipomoea lacunosa L.) and large crabgrass [ Digitaria sanguinalis (L.) Scop.]. Corn and soybean yield increased as both cover crop biomass and C:N ratio increased where no weed control measures were implemented beyond cover crop. The same trend was observed with cash crop yield in the weed-free subblocks, with one exception. This research indicates that cover crop residue composition is important for weed control in addition to biomass.